Operational assessment of continuous flow intersections in a connected vehicle environment. Issue 6 (18th August 2022) - Alzoubaidi, Mutasem; Zlatkovic, Milan
ABSTRACT: In this study, the operational performance of the joint deployment of Connected Vehicles (CVs) and Continuous Flow Intersections (CFIs) is evaluated in a simulation environment built using VISSIM. The operational effect of various Market Penetration Rates (MPRs) of CVs at full and partial CFIs is studied. CV communication protocols that help exchange vehicles' and signal controllers' latitude/longitude coordinates via the Vehicle-to-Infrastructure communications are developed, programmed in Python and deployed in the VISSIM's models. Additionally, two-tailed t-tests were conducted to examine the statistical significance of the results. The findings indicate that the deployment of CV technology at CFIs improved the overall operational performance substantially for all the studied scenarios and performance measures. Specifically, travel times, delays and queue lengths were reduced by 65.3%, 29.2% and 57.8%, respectively, at the 100% MPR. It was found that higher MPRs would lead to greater operational benefits.